Obtaining diverse behaviors in a climate model without the use of flux adjustments. Issue 7 (9th April 2013) - Yamazaki, Kuniko; Rowlands, Daniel J.; Aina, Tolu; Blaker, Adam T.; Bowery, Andy; Massey, Neil; Miller, Jonathan; Rye, Cameron; Tett, Simon F. B.; Williamson, Daniel; Yamazaki, Yasuhiro H.; Allen, Myles R.
Abstract: [1] A number of studies have set out to obtain a range of atmosphere and ocean model behavior by perturbing parameters in a single climate model (perturbed physics ensemble: PPE). Early studies used shallow layer slab ocean or flux‐adjusted coupled ocean‐atmosphere models to obtain a broad range of behavior as characterized by climate sensitivity. A recent study reports a relatively narrow range of sensitivities (2.2–3.2°C) in a PPE of 35 coupled models without flux adjustment, raising the question whether previous broad ranges were an artifact of the use of models that were not in top‐of‐atmosphere (TOA) energy balance. Moreover, no PPE experiment has reported a large spread of behavior of the ocean compared to that exhibited in a multi‐model ensemble (MME) such as Coupled Model Intercomparison Project phase 3 (CMIP3). In this work, we randomly perturb model parameters of a coupled ocean‐atmosphere general circulation model using a space‐filling design containing 10, 000 combinations. The ensemble is run over the distributed computing platform of climateprediction.net under fixed pre‐industrial forcing without flux adjustment. We resample a second, 20, 000‐member, ensemble with perturbations conditioned on the TOA fluxes from the first ensemble to not drift significantly from a realistic base state while targeting a range of behavior. Models within the targeted ensemble show realistic regional control climates when compared to the CMIP3 ensemble, although there is a bias in global mean surface temperature. The range of predicted equilibrium climate sensitivities of the targeted ensemble is substantially smaller than that obtained with flux adjustment, but larger than the range in the CMIP3 ensemble or in the 35‐model un‐flux‐adjusted PPE in a recent study mentioned above. The Atlantic meridional overturning circulation in the targeted ensemble exhibits a spread in strength as wide as that found in the CMIP3 ensemble. We conclude that flux adjustment is not a pre‐requisite for obtaining a broad spread of behavior in a perturbed physics ensemble. Key Points: Flux adjustment is not a pre‐requisite for a broad spread of behavior in a PPE.